Observation of a Cu(II)(2)(μ-1,2-peroxo)/Cu(III)(2)(μ-oxo)(2) Equilibrium and its Implications for Copper-Dioxygen Reactivity() - Kieber-Emmons, Matthew T. (2014)
Synthesis of small molecule Cu(2)O(2) adducts has provided insight into the related biological systems and their reactivity patterns including the interconversion of the Cu(II)(2)(μ-η(2):η(2)-peroxo) and Cu(III)(2)(μ-oxo)(2) isomers. In this study, absorption spectroscopy, kinetics, and resonance Raman data show that the oxygenated product of [(BQPA)Cu(I)](+) initially yields an “end-on peroxo” species, that subsequently converts to the thermodynamically more stable “bis-μ-oxo” isomer (K(eq) = 3.2 at −90 °C). Calibration of density functional theory calculations to these experimental data suggest that the electrophilic reactivity previously ascribed to end-on peroxo species is in fact a result of an accessible bis-μ-oxo isomer, an electrophilic Cu(2)O(2) isomer in contrast to the nucleophilic reactivity of binuclear Cu(II) end-on peroxo species. This study is the first report of the interconversion of an end-on peroxo to bis-μ-oxo species in transition metal-dioxygen chemistry.